Sexual and reproductive health in the new undergraduate and postgraduate medical education curriculum of the Peruvian physician - Mascaro Sánchez, Pedro (2018)
As is known, university education requires a permanent evaluation and analysis to respond with relevance to the dynamics and local and global changes, such as needs and rights of the inhabitants of the planet so that they keep the balance and reach the development from the knowledge. This task is increased as the so-called 'globalization time' which we attend irreversibly involves economic, political, social and cultural processes, among others, constituting an integral and dynamic phenomenon that affects contemporary society, generating great inequalities and posing great challenges to the academy.